Enhanced activity of silver modified thin-film TiO2 photocatalysts - P. Falaras; I. M. Arabatzis; T. Stergiopoulos; M. C. Bernard (International Journal of Photoenergy)
Novel, composite silver/titania immobilized on glass substrates were prepared, characterized and their photocatalytic activity was evaluated. The undoped original material consists of rough, high surface area nanocrystalline titanium dioxide (TiO2) thin films. To increase their efficiency, the TiO2 films were modified by silver cations deposition and subsequent UV-C irradiation. SEM pictures confirmed the existence of an open porous network of interconnected titania particles on the semiconductor surface. AFM analysis proved the presence of spherical silver particles on the catalyst surface and provided quantitative surface parameters as fractal dimension, surface roughness and mean particle diameter. Spectroreflectometry showed the presence of an increase in optical absorbance attributed to plasmon resonance absorption of the silver clusters. The photocatalytic properties of the surface modified materials were investigated through photodegradation of Methyl Orange. The silver deposition conditions were optimized for maximum photocatalytic efficiency and crucial parameters such as dipping period, UV irradiation time, and concentration of the dipping solution were determined. The optimum silver nitrate concentration of the dipping solution was found to be 10-3 M. This silver doped photocatalyst decomposes the azo-dye pollutant 3-times faster than the un-doped Degussa P25 TiO2 film. A concentration increase results in a decrease of the films photocatalytic performance. Strength and reproducibility tests proved that the photocatalytic activity of the silver doped titania was perfectly reproducible.